The Experience of Lithuanian University of Educational Sciences Students on Pedagogical Practices: Pupil Behaviour Observation - Trakšelys, Kęstutis (Pedagogika, 2015)
Behaviour is usually named as a main and the essential educational stimulus in the lesson. Due to the pupils’ inappropriate behaviour is common to blame their unwillingness to learn, laziness or period of adolescence. Teachers are usually looking for various types of abnormal behavior and other disorders in their pupils. Students who had teacher‘s assistant practice at schools were observing pupils and their teachers interaction in lessons. The observed lessons’ data show that lots of impact for pupil’s behaviour has teacher’s personality, the ability to communicate, respect and interact with them. The appropriate teaching organization, the competence to explain the aims and goals of the task, ability to select suitable teaching / learning methods, didactic attitude, the ability to control emotional intelligence and ect. According to reports of students, who had pedagogical teacher’s assistant practice at these schools, teachers not always give well suited teaching material. It doesn’t correspond to the pupils in his / her needs, interests, and expectations. Thy don‘t want and can‘t concentrate attention for 45 minutes. Sometimes happen when the teacher has wrong planned lessons, then pupils waste their time because simply they don‘t have what to do. The results show that very low percent of pupils work effectively, have high quality knowledge and learning results. In many cases teachers do not create positive learning environment, fail to ensure emotional security by threatening to write negative marks, to send away from classroom or end the lesson. Teachers usually don’t pay enough attention for their pupils for many reasons. They prefer treating these who are more motivated to study or are going to take the exam of the curriculum. Behaving in this way teachers make all conditions for unwillingness to study and provoke inappropriate activity of their students during lessons. In such conditions the educators don’t involve pupils of all social groups. It means that integration doesn’t work for children with the special needs. Also doesn’t work so called the inclusive education. Thy do not ensure pleasant microclimate in the classroom and suitable educational environment. The observation results state that some educators of these schools acted inadequate by writing negative marks for the students who tried to show inappropriate behaviour. Also we should emphasize that some teachers and students, who had teacher’s assistant practice, lack abilities to adapt their pedagogical and psychological knowledge in their work with pupils. They lack of abilities to control the audience, to interact with the pupils. Also they lack skills of working in a stratified society.